Stressors and Resources for Healthcare Professionals During the Covid-19 Pandemic: Lesson Learned From Italy - Barello, Serena; Palamenghi, Lorenzo; Graffigna, Guendalina (Frontiers in Psychology, 2020)
The COVID-19 pandemic is exerting a high pressure on healthcare systems all over the world. Italy, in particular, being one of the first Western countries to be struck by the contagion, has seen the number of recovered -and deceased- patients increase alarmingly, thus increasing the workload and the demands for healthcare professionals. This situation has the potential to put several healthcare operators at risk of developing high levels of work-related distress and burnout due to the exposure to emotionally difficult situations, uncertainty, and personal risk. A sample of 532 Italian physicians, nurses, and other professionals answered an online survey addressing their levels of burnout (through the Maslach Burnout Inventory) and frequency of experienced psycho-somatic symptoms, along with some ad hoc items regarding job demands. Results show that levels of burnout and experienced symptoms are correlated with the increased demands due to the COVID-19 pandemic, while finding a meaning in one’s own work is correlated with personal gratification. Urgent measures to address concerns regarding the wellbeing of health workers are a necessary key point of the response to the current pandemic.